Catalytic effect of Ni@rGO on the hydrogen storage properties of MgH2 - Pengyang Yao; Ying Jiang; Yang Liu; Chengzhang Wu; Kuo-Chih Chou; Tao Lyu; Qian Li (Journal of Magnesium and Alloys, 2020)
Uniform-dispersed Ni nanoparticles (NPs) anchored on reduced graphene oxide (Ni@rGO) catalyzed MgH2 (MH-Ni@rGO) has been fabricated by mechanical milling. The effects of milling time and Ni loading amount on the hydrogen storage properties of MgH2 have been investigated. The initial hydrogen desorption temperature of MgH2 catalyzed by 10 wt.% Ni4@rGO6 for milling 5 h is significantly decreased from 251 °C to 190 °C. The composite can absorb 5.0 wt.% hydrogen in 20 min at 100 °C, while it can desorb 6.1 wt.% within 15 min at 300 °C. Through the investigation of the phase transformation and dehydrogenation kinetics during hydrogen ab/desorption cycles, we found that the in-situ formed Mg2Ni/Mg2NiH4 exhibited better catalytic effect than Ni. When Ni loading amount is 45 wt.%, the rGO in Ni@rGO catalysts can prevent the reaction of Ni and Mg due to the strong interaction between rGO and Ni NPs.